The hematological profile of Barbonymus altus to evaluate water quality in the Badher Bank Conservation Area, Blitar, East Java, Indonesia - Asus Maizar Suryanto Hertika; Supriatna Supriatna; Arief Darmawan; Bimo Aji Nugroho; Agung Dwi Handoko; Agustiansi Yeyen Qurniawatri; Ranita Ayu Prasetyawati (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Hertika AMS, Supriatna, Darmawan A, Nugroho BA, Handoko AD, Qurniawatri AY, Prasetyawati RA. 2021. The hematological profile of Badher fish (Barbonymus altus) to evaluate water quality in the Badher Bank Conservation Area, Tawangrejo Village, Blitar District, East Java, Indonesia. Biodiversitas 22: 2532-2541. Badher fish (Barbonymus altus) is endemic to the Brantas River. After years presumably extinct, the Badher fish was found again in 2010 in the Brantas River, Tawangrejo Village, Binangun Sub-district, Blitar District, East Java, Indonesia. A conservation area, called a Badher Bank, was established in the location. However, human activities, such as ecotourism and agricultural waste runoff, have changed water quality and increased water pollution in the Badher Bank Conservation Area. This research objective was to observe the hematological profile of badher fish and a set of water quality parameter measurements as an environmental factor that affected fish life. Data were obtained from four research stations with three replications every two weeks from August to October 2020 at the Brantas River streamline inside the Badher Bank Conservation Area. The Canonical Correspondence Analysis (CCA) method was applied to determine the correlation between water quality and hematological profile. According to the data analysis, the water quality at Stations 1-3 in the research location was normal, and Station 4 was polluted. The analysis also showed that the low dissolved oxygen and high ammonia affected the hematological conditions of Badher fish. All water quality parameters affected the condition of leucocytes, erythrocytes, and hemoglobin in moderate concentrations. Besides that, micronuclei and hematocrit conditions were strongly influenced by ammonia, temperature, pH, and current velocity in high concentrations, while Dissolved Oxygen (DO) and Total Suspended Solid (TSS) affected low concentrations.